Tantangan yang Dihadapi Kepala Sekolah dan Guru dalam Melaksanakan Supervise - M. Ramli Alfarisi (Badan Penerbit STIEPARI Press, 2025)
This research discusses the challenges faced by school principals and teachers in the implementation of supervision in the educational environment. Supervision has an important role in improving the quality of teaching and teacher professionalism, but it is often constrained by limited resources, administrative burdens, policy changes, and limited information technology competencies. In addition, teachers often face pressure and resistance to supervision that can hinder the achievement of the goal of improving the quality of learning. Through a literature review, this study identifies strategies that can overcome these challenges, such as the use of technology to support administrative tasks, supervision training for principals, and the application of collaborative and reflective approaches. It is hoped that the findings of this study can provide practical recommendations in creating a more effective supervision process and supporting the improvement of the quality of education in schools.